Mapping and Dynamics of Regulatory DNA in Maturing Arabidopsis thaliana Siliques - Sullivan, Alessandra M.; Arsovski, Andrej A.; Thompson, Agnieszka; Sandstrom, Richard; Thurman, Robert E.; Neph, Shane; Johnson, Audra K.; Sullivan, Shawn T.; Sabo, Peter J.; Neri, Fidencio V.; Weaver, Molly; Diegel, Morgan; et al. (Frontiers in Plant Science, 2019)
The genome is reprogrammed during development to produce diverse cell types, largely through altered expression and activity of key transcription factors. The accessibility and critical functions of epidermal cells have made them a model for connecting transcriptional events to development in a range of model systems. In Arabidopsis thaliana and many other plants, fertilization triggers differentiation of specialized epidermal seed coat cells that have a unique morphology caused by large extracellular deposits of polysaccharides. Here, we used DNase I-seq to generate regulatory landscapes of A. thaliana seeds at two critical time points in seed coat maturation (4DPA and 7DPA), enriching for seed coat cells with the INTACT method. We found over 3000 developmentally dynamic regulatory DNA elements and explored their relationship with nearby gene expression. The dynamic regulatory elements were enriched for motifs for several transcription factors families; most notably the TCP family at the earlier time point and the MYB family at the later one. To assess the extent to which the observed regulatory sites in seeds added to previously known regulatory sites in A. thaliana, we compared our data to 11 other data sets generated with seven-day-old seedlings for diverse tissues and conditions. Surprisingly, over a quarter of the regulatory, i.e. accessible, bases observed in seeds were novel. Notably, plant regulatory landscapes from different tissues, cell types or developmental stages were more dynamic than those generated from bulk tissue in response to environmental perturbations, highlighting the importance of extending studies of regulatory DNA to single tissues and cell types during development.